A case of aberrant post-breeding moult coinciding with nest desertion in a female Common Tern - Braasch, Alexander (2012)
In the annual cycle of migratory birds, the initiation of moult needs to be adjusted to other important processes, such as migration and reproduction, which are controlled by endogenous circannual rhythms. In the Common Tern Sterna hirundo, it has been widely recognized that moult cycles are typically slow and differ among individuals, resulting in a large overlap of nearly all age-dependent plumage features in the annual cycle. Here we report a case of early post-breeding moult coinciding with nest desertion in an adult female Common Tern. Observations were made in 2008 at the Common Tern colony ’Banter See’ situated within the harbour area of Wilhelmshaven on the German North Sea coast. The annual recurrence of an early post-breeding moult within an individual of known age underlines the large possible overlap of plumages within a breeding population. Furthermore, it gives a good example how the timing of moult of single birds may be controlled by intrinsic physiological processes. In the case of this particular individual, a decrease in prolactin concentrations associated with an attenuation of incubation behaviour might have caused nest desertion and initiated moult.